’’Should the child be raised as male or female?’’ The evaluation and management of different causes of ambiguous genital appearance in children - Al Khanjari, Salma; Al Balushi, Malak Saleem; Kanojia, Ravi Prakash; Al Sajwani, Mohammed Jaffer (The European Research Journal, 2023)
Diagnosing, managing and assigning gender for different causes of ambiguous genitalia in children can be challenging. This article will discuss about the types, diagnosis and treatment of disorders of sex development including congenital adrenal hyperplasia, 46 XY mixed gonadal dysgenesis and 46XY ovotesticular disorder of sex development. This article reports about 3 cases of disorders of sex development. The first case is about a three-year-old girl who was diagnosed with congenital adrenal hyperplasia, genital examination revealed clitoromegaly and a single urogenital sinus; she was managed medically and surgically. The second case is about a one-month-old child with 46XY karyotype, genital examination revealed penoscrotal hypospadias with right palpable and left impalpable gonads. Patient underwent diagnostic laparoscopy in which both female and male internal organs were found; based on these results a diagnosis of 46XY ovotesticular disorder of sex development was made. The third case is about a 3-month-old child with 46XY karyotype, genital examination revealed hypospadias with bilateral impalpable gonads. Diagnostic laparoscopy showed a uterus with a bilateral ovary-looking gonad; histopathology of the bilateral ovary-looking gonads was consistent with testicular tissue. Based on the above, a diagnosis of 46XY mixed gonadal dysgenesis was made. Disorders of sex development are classified into three main categories based on the karyotype, XX, XY and sex chromosome other than XX and XY. Laboratory investigations, karyotype, genetic analysis, imaging, surgery and tissue biopsy, all aid in diagnosing, deciding gender identity and managing different types of disorders of sex development.